Ongoing decline in genital warts among young heterosexuals 7 years after the Australian human papillomavirus (HPV) vaccination programme. (10th October 2014) - Chow, Eric P F; Read, Tim R H; Wigan, Rebecca; Donovan, Basil; Chen, Marcus Y; Bradshaw, Catriona S; Fairley, Christopher K
Abstract : Background: Australia has provided free quadrivalent human papillomavirus (HPV) vaccines to school girls since mid-2007 and a catch-up programme in the community to women aged up to 26 years in 2007–2009. We describe the temporal trend of genital warts in different populations in Melbourne. Methods: We analysed the proportion diagnosed with genital warts for all new patients attending Melbourne Sexual Health Centre from July 2004 to June 2014, stratified by different risk groups and age. Adjusted ORs were calculated to compare the annual trend in the proportion of patients with genital warts in different risk groups in the prevaccination period (before June 2007) and the vaccination period (after July 2007). Results: The proportion with genital warts decreased in women aged <21 years, from 18.4% in 2004/2005 to 1.1% in 2013/2014 (p<0.001), but increased in women aged >32 years, from 4.0% to 8.5% (p=0.037). The odds per year for diagnosis of genital warts adjusted for number of sexual partners in the vaccination period were 0.55 (95% CI 0.47 to 0.65) and 0.63 (95% CI 0.54 to 0.74) in women and heterosexual men aged <21 years, respectively. There was no change in adjusted odds of genital warts in both women and men aged >32 years. A small annual decline in genital warts was observed in men who have sex with men (aOR=0.92; 95% CI 0.88 to 0.97). Conclusions: Genital warts have now become rare in young Australian women and heterosexual men 7 years after the launch of the national HPV vaccination programme but in stark contrast, remain common in men who have sex with men.